Exploration of discharge planning components in heart failure patients: A literature review - Amoy Amelia Sanusi; Wan Nishfa Dewi; Bayhakki Bayhakki (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Discharge planning is a major focus of healthcare systems worldwide. Coordinating services from the hospital to the community, ensuring smooth patient discharge, reducing length of stay (LOS) in the hospital, and reducing patient readmission rates. Purpose: To explore the components discharge planningin heart failure patients. Method: A systematic search for relevant peer-reviewed articles was conducted using electronic database sources. This literature review used 10 qualitative journal articles obtained through ProQuest, ScienceDirect, and ClinicalKey with a publication period of 2020-2024 using the keywords “exploration” AND “discharge planning” AND “heart failure”. Results: The analysis showed that discharge planning programs were effective in reducing the number of readmission days in the hospital compared to the previous duration of care. In addition, this program also increased patient compliance in taking medication, expanded knowledge about self-care management for heart failure patients at home, and reduced treatment costs. Conclusion: The integration of these key components in discharge planning can increase the success of heart failure patient care and prevent re-hospitalization. Recommendation: It is expected that discharge planning can be applied in all inpatient services to reduce readmissions, especially in heart failure patients.